Cost-effectiveness of a specialist geriatric medical intervention for frail older people discharged from acute medical units: economic evaluation in a two-centre randomised controlled trial (AMIGOS) - Bayer, Antony; Tanajewski, Lukasz; Franklin, Matthew; Gkountouras, Georgios; Berdunov, Vladislav; Edmans, Judi; Conroy, Simon; Bradshaw, Lucy E.; Gladman, John R.F.; Elliott, Rachel (Public Library of Science, 2015)
Background Poor outcomes and high resource-use are observed for frail older people discharged from acute medical units. A specialist geriatric medical intervention, to facilitate Comprehensive Geriatric Assessment, was developed to reduce the incidence of adverse outcomes and associated high resource-use in this group in the post-discharge period.